On oligarchy : ancient lessons for global politics - Tabachnick, David Edward, 1972-; Koivukoski, Toivo (University of Toronto Press, 2011)
"Economic power is becoming increasingly concentrated in the hands of the few, even as democratic movements worldwide allow for political power to be dispersed among the many. With their access to influence, the wealthy can shape and constrain the political power of the rest of the world. As the economic dominance of an elite minority coincides with the forces of globalization, is oligarchy becoming the dominant political regime? This collection explores the renewed relevance of oligarchy to contemporary global politics. By drawing out lessons from classic texts, contributors illustrate how the character of oligarchical regimes informs contemporary political life. Topics include the relationship between the American government and corporations, the tension between republican and oligarchical regimes, and the potential conflicts that have opened up between economic management and political life. On Oligarchy deftly illuminates the significance of this regime in the context of pressing global economic and political issues."--The publisher